Hiding the Vector Resonance Signal Hiding the Vector Resonance Signal - Gintner, Mikulas; Juran, Josef (Communications - Scientific Letters of the University of Zilina, 2014)
We investigate how the interplay of the direct and mixing-induced couplings of the hypothetical SU(2)L+R vector triplet resonance to the third quark generation can hide the resonance signal in ,tb tb , and / bt tb channels. The vector resonances are assumed to represent bound states of hypothetical strongly-interacting new physics, the extension of the Standard model.
Keywords: electroweak symmetry breaking; effective Lagrangian; vector resonances; new strong interactions